Penyuluhan Pentingnya Menjaga Kesehatan dan Merawat Kebersihan Gigi Tiruan di Panti Werdha Wisma Mulia - Yayuk Yuliarsi; Wiwiek Poedjiastoeti; Didi Nugroho Santosa; Bernard O. Iskandar; Monica Dewi Ranggaini (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
The impact of the Covid-19 has made the elderly's access to dental and oral health even more limited. Oral hygiene in the elderly living in nursing homes is often ignored so it falls into the poor category. The high prevalence of caries and other dental problems makes the elderly need more dental treatment. Poor oral health can lead into systemic or local infections that will affect general health, especially in the elderly who have impaired physiologic or pathologic function. Increased knowledge will improve their oral hygiene. Therefore, to increase members' knowledge and awareness to oral health, FKG Trisakti held an education to maintain their oral health and dentures. Pre and post tests are given to the participants to determine the success of the education. T test result showed increase in knowledge from participants before and after giving the material. Further training can be given to caregivers as they were there to help the elderly maintain their oral care.